Los pictogramas como recurso para facilitar la comprensión oral y escrita en los estudiantes de primer grado de Educación General Básica - Castillo Girón, Mercedes Petronila (2022)
One of the main problems facing education today is the lack of oral and written comprehension in basic education students, which is dragging them to higher levels of schooling; In this sense, the main objective of this work was to facilitate oral and written comprehension in first grade students through the implementation of pictograms in the teaching-learning process. The research approach used was mixed, with a cross-sectional design and with a population of seven children attending first grade. The procedure was carried out in three aspects: the pictograms were characterized as resources that facilitated oral and written comprehension; the contribution of pictograms was established as a resource in the teaching-learning process to facilitate oral and written comprehension; and, methodological guidelines on the use of pictograms in the teaching-learning process were proposed to facilitate oral and written comprehension in first grade students. The methods used were inductive and analytical-synthetic; the technique used was the survey and the instrument the questionnaire. As results, it is highlighted that pictograms really have many advantages that, if used properly, achieve oral and written comprehension in children; Similarly, the results show benefits in the didactic, methodological and pedagogical order for the teachers; while in the student oral and written comprehension is enhanced, as well as their holistic development. It is concluded that pictograms are an effective means to stimulate the teaching-learning process and facilitate oral and written comprehension. Keywords: Learning, teaching, pictograms, professional mysticism.